Analisis Sistem Pembumian Tower Dengan Menggunakan Mesh Grid Grounding Pada T.213 SUTT 70 kV Pekalongan - Sukamerindu - Erawati Purnama Panjaitan; Parlin Siagian; Siti Anisah (Jurnal Multidisiplin Dehasen (MUDE), 2026)
The grounding system is an important part of maintaining the safety and reliability of electrical power transmission systems, especially in high-voltage transmission towers. In transmission towers, the grounding system functions to safely conduct fault currents caused by lightning strikes or short circuits to the ground. This study aims to analyze the grounding system of a 70 kV transmission tower using the Mesh Grid Grounding System (MGGS) method on Tower T.213 of the Pekalongan - Sukamerindu line. The research method used is a quantitative method with a technical analysis approach, namely calculating the grounding resistance of the grid system, the ground rod system, and the total MGGS grounding resistance based on field data. The data used included soil resistivity of 48.7 Ωm, grid conductor length of 66 m, grid area of 36 m², conductor planting depth of 1 m, and the use of 20 ground rods with a length of 2 m. The calculation results were then compared with the field measurement results to determine the reliability level of the grounding system. The results of the study show that the initial grounding resistance value of 8.46 Ω can be reduced to 4.46 Ω after applying the MGGS method. The reduction in grounding resistance value reached 47.3%, indicating that the MGGS method is effective in improving the performance of the tower grounding system. Based on an evaluation of the IEEE Std 80 standard, the final grounding resistance value obtained was still below the recommended maximum limit, so the grounding system of Tower T.213 was declared safe and suitable for use. Thus, the application of the Mesh Grid Grounding System (MGGS) method has been proven to improve the reliability and safety of the grounding system on 70 kV transmission towers.